Three-Phase Symmetrical Multilevel Converter for Grid-Connected PV Systems: Enhancing Power Quality and Efficiency in Distributed Generation (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In this paper, we present a new three-phase symmetrical multilevel converter for grid-connected systems using a PV source. Renewable energy sources are the application of distributed generation (DG) in the distribution system and have gained more attention. The distribution generation systems are powered by microsources such as fuel cells, photovoltaic (PV) systems, and batteries. PV-distributed system in which the solar source is low-dc input voltage interfaced to the grid using front-end conversion. Three-phase Cascaded H-Bridge A seven-level inverter is interfaced with a low-frequency transformer with multiple PV sources. Nowadays, multilevel inverters (MLI) play a vital role in the field of power electronics and are widely used in many industrial and commercial applications. Moreover, advantages like high-quality power output, low switching losses, low electro-magnetic interference (EMI), and high output voltage make multilevel inverters a powerful solution in converter topology.